Who eats what? : food chains and food webs - Lauber, Patricia; Keller, Holly (New York, NY : HarperCollins, 1995)
Explains the concept of a food chain and how plants, animals, and humans are ecologically linked.
Keywords: Food chains (Ecology) -- Juvenile literature; Food chains (Ecology); Ecology; Juvenile works